Application of Adams-Bashforth-Moulton Method on Logistic Equation in Predicting Population Growth - Alorgbey, Bernard; Abdullah, Sumarni; Njoroge, Paul Kahenya; Rewili, Yusra (Interval: Indonesian Journal of Mathematical Education, 2025)
Purpose of the study: This study aims to obtain population growth prediction results using the Adams-Bashforth-Moulton method. Methodology: This type of research is applied research. In this study, the Adams-Bashforth-Moulton method was applied by solving the problem of population growth in South Sulawesi Province. Main Findings: The logistic equation for population growth with a step size of h = 1 and the capacity of South Sulawesi Province is 20,000,000 people, with a growth rate of 2%. The numerical solution of the logistic equation for population growth at time t = 2020 with an optimal step size of ℎ = 1 is 8,944,168 people. Novelty/Originality of this study: This research is unique in the form of applying the Adams-Bashforth-Moulton method to solve problems in calculating population growth in South Sulawesi Province.